1982
DOI: 10.1093/ajcn/36.4.617
|View full text |Cite
|
Sign up to set email alerts
|

Eggs, serum cholesterol, and coronary heart disease

Abstract: The Framingham Study has investigated the effect of host and environmental factors on the development of coronary heart disease since 1949. Serum cholesterol level was determined to the one of the risk factors for coronary heart disease. The nutrient intake, in a subsample of the study population, was determined in 1957. A review of this material has permitted an estimate of egg consumption on each of 912 subjects. The serum cholesterol distribution curves of the subjects according to tertile of egg intake wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(66 citation statements)
references
References 15 publications
3
61
0
2
Order By: Relevance
“…In an earlier study it was also concluded that differences in egg consumption were unrelated to blood cholesterol level or to coronary heart disease incidence (Dawber et al, 1982). This is in agreement with another study in humans suggesting that a moderate egg intake should not be rigorously restricted in healthy individuals (Schnohr et al, 1994).…”
Section: Nutrient Stabilitysupporting
confidence: 78%
“…In an earlier study it was also concluded that differences in egg consumption were unrelated to blood cholesterol level or to coronary heart disease incidence (Dawber et al, 1982). This is in agreement with another study in humans suggesting that a moderate egg intake should not be rigorously restricted in healthy individuals (Schnohr et al, 1994).…”
Section: Nutrient Stabilitysupporting
confidence: 78%
“…It is widely accepted that diets high in saturated fat increase the risk of CHD [52][53][54], and there is a fairly broad-based consensus on the role of dietary fat (especially saturated fatty acids) in hyperlipidemia and on the role of hyperlipidemia in CHD. Patients with diabetes are particularly vulnerable to CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the relationship between diet and CHD has been studied intensively. Studies on diet quality and CHD have focused largely on determining the dietary risk factors of CHD (6)(7)(8)(9)(10)(11)(12). Accordingly, dietary risk factors for CVD are diets high in saturated and trans fat and low in polyunsaturated fatty acids, vegetables, fruits, and fiber (13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Dietary Quality After Diagnosis Of Coronary Heart Diseasementioning
confidence: 99%